Anion and cation substitution in transition-metal oxides nanosheets for high-performance hybrid supercapacitors - Li, Jinghua; Liu, Zaichun; Zhang, Qiaobao; Cheng, Yong; Zhao, Bote; Dai, Shuge; Wu, Hong-Hui; Zhang, Kaili; Ding, Dong; Wu, Yuping; Liu, Meilin; Wang, Ming-Sheng (Nano energy, 2019)
Anion and cation substitution is an effective way in modulating electrochemical properties of electrode materials to achieve enhanced performance. Herein, we report our finding in the fabrication of advanced binder-free supercapacitor electrodes of hierarchical anion- (phosphorus-) and cation- (zinc- and nickel-) substituted cobalt oxides (denoted as ZnNiCo-P) architectures assembled from nanosheets grown directly on Ni foam. In contrast to the reference Co-P systems, the as-prepared electrode manifests a markedly improved electrochemical performance with a high specific capacity of ~ 958 C g−1 at 1 A g−1 and an outstanding rate capability (787 C g−1 at 20 A g−1) due to its compositional and structural advantages. Density functional theory calculations confirm that the Co species partially replaced by Zn/Ni and O species by P can simultaneously improve the charge transfer behavior and facilitate the OH- adsorption and deprotonation/protonation reaction process. Moreover, an aqueous hybrid supercapacitor based on self-supported ZnNiCo-P nanosheet electrode demonstrates a high energy density of 60.1 Wh kg−1 at a power density of 960 W kg−1, along with a superior cycling performance (89% of initial specific capacitance after 8000 cycles at 10 A g−1 is retained). These findings offer insights into the rational design of transition metal compounds with multi-components and favorable architectures by manipulating the cations and anions of metal compounds for high-performance supercapacitors. A high-performance mix-metal phosphide nanosheet electrode enables excellent capacity, rate capability, and cycle stability of hybrid supercapacitors. The electrode is composed of hierarchical Zn and Ni co-substituted Co phosphide nanosheet arrays grown on porous Ni foam. [Display omitted] •Hierarchical ZnNiCo-P nanosheet arrays grown directly on Ni foam are constructed for the first time.•The resultant binder-free electrodes manifest outstanding electrochemical performances.•The synergetic contribution and structural features together contribute to outstanding electrochemical performance.•The assembled ZnNiCo-P//PPD-rGOs hybrid supercapacitor achieved a high energy density of 60.1 W h kg−1 at a power density of 960 W kg−1.